A single-molecule ELISA device utilizing nanofluidics. Issue 4 (24th January 2018) - Shirai, Kentaro; Mawatari, Kazuma; Ohta, Ryoichi; Shimizu, Hisashi; Kitamori, Takehiko
Abstract : Single molecule analysis is desired in many areas that require the analysis of ultra-small volume and/or extremely low concentration samples ( e.g., single-cell biology, medicine diagnosis, virus detection, etc .). Abstract : Single molecule analysis is desired in many areas that require the analysis of ultra-small volume and/or extremely low concentration samples ( e.g., single-cell biology, medicine diagnosis, virus detection, etc .). Due to the ultra-small volume or concentration, the sample contains only single or countable analyte molecules. Thus, specific single molecules should be precisely processed and detected for analysis. However, except nucleic acids, most molecules are difficult to amplify, and a new analytical methodology for specific single molecules is thus essential. For this, efficient chemical processing and detection, which are important analytical elements, should be developed. Here, we report a single-molecule ELISA (enzyme-linked immunosorbent assay) device utilizing micro/nanofluidic technology. Both chemical processing and detection were integrated into an ultra-small space (10 2 nm in size), and the integration allowed precise processing (∼100% capture) and detection of a specific single molecule (protein) for the first time. This new concept and enabling technology represent a significant innovation in analytical chemistry and will have a large impact on general biology and medicine.